PENGEMBANGAN MODEL BUKU PELAJARAN BAHASA INDONESIA BERBASIS PEMBELAJARAN KONTEKSTUAL - Suryaman, Maman (Diksi, 2015)
This article is about a research with the objective of discovering a model for a course book based on contextual instruction for junior high school classes of Indonesian. To achieve the objective, in the first phase of the research, that is, in the first year, 2007, the research had the specific objective of discovering manifestations of contextual instruction to serve as starting points in developing the model. The research subjects consisted of (1) class instruction, (2) students, and (3) course books of Indonesian. The research results indicated the following. (1) When a constructive strategy is used, the contextual manifestations are, among others, simple formulations of objectives, uses of operational verbs, the appearance of themes, the mapping of new experiences, an appropriateness of the strategy and method from the point of objectives and learners' characteristics, and language suitability. (2) When an inquiry strategy is used, the manifestations are, among others, a match between objectives and thematic basic competency indicators, consideration of learners' needs, appropriate selection of media, appropriateness of the strategy and method from the point of learners' needs, hypothesis confirmation or testing, and gain of new experience. (3) When a question-and-answer strategy is used, the manifestations are, among others, apperception, questions and answers, encouragement through questions, and asking resource persons questions. (4) When a modeling strategy is used, the manifestations consist of imitation, giving examples, making use of examples, and variety of examples. (5) When a learningcommunity strategy is used, the manifestations consist of the discovery of new experience, problem-solving through group work, development of selfdependence as well as collaborative work, communication of learning results to others, communication of works to others, and ethical formation. (6) When an authentic-assessment strategy is used, the manifestations consist of variety in method of assessment, presentation of work, and work performance. (7) When a reflection strategy is used, the manifestations consist of linking learning results with benefits for learners, self-development, expansion of experience, pursuit of meaning, creation of a feeling of pleasure, support of what one dreams to achieve, and creation of motivation. (8) The anatomy of the course book consists of (a) the introduction, containing the title of the book, preface, table of contents, and organization of content, (b) the content, containing the material, material presentation, and strategy of presentation, and (c) the conclusion, containing the evaluation, reflection, bibliography, index, and relevant answer keys. Keywords: course book, contextual manifestations and strategies